2019
DOI: 10.1007/s40261-019-00835-z
|View full text |Cite
|
Sign up to set email alerts
|

The Respimat® Soft Mist Inhaler: Implications of Drug Delivery Characteristics for Patients

Abstract: Successful treatment for respiratory diseases relies on effective delivery of medication to the lungs using an inhalation device. Different inhalers have distinct characteristics affecting drug administration and patient adherence, which can impact clinical outcomes. We report on the development of the Respimat® soft mist inhaler (SMI) and compare key attributes with metered-dose inhalers (MDIs) and dry powder inhalers (DPIs). The Respimat SMI, a pocket-sized device generating a single-breath, inhalable aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 51 publications
(99 reference statements)
0
36
0
1
Order By: Relevance
“…These results provide support for benefits of nebulization in a wider set of patients who may show variable tidal volumes and breathing patterns, whereas DPIs may be more beneficial among patients who are capable of generating the required, device-specific PIF consistently. It is important to note that TIO is also available for delivery using an SMI, which may provide greater advantages for patients having similar breathing patterns to those tested in this study, as SMIs have been shown to have a higher in vitro deposition compared to other inhalers [29,39,40]. The timing of this study in the summer of 2019 coincided with a period in which the HandiHalerÒ was predominantly used for delivery of TIO, and as such led to the use of the HandiHalerÒ as a comparator device in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide support for benefits of nebulization in a wider set of patients who may show variable tidal volumes and breathing patterns, whereas DPIs may be more beneficial among patients who are capable of generating the required, device-specific PIF consistently. It is important to note that TIO is also available for delivery using an SMI, which may provide greater advantages for patients having similar breathing patterns to those tested in this study, as SMIs have been shown to have a higher in vitro deposition compared to other inhalers [29,39,40]. The timing of this study in the summer of 2019 coincided with a period in which the HandiHalerÒ was predominantly used for delivery of TIO, and as such led to the use of the HandiHalerÒ as a comparator device in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ethanol in the solutions delivered from the Respimat™ soft mist inhaler, e.g. tiotropium (Spiriva®, Boehringer Ingelheim) enhances the solubilization properties of the medium and facilitates a hand held aqueous based system with accurate and reproducible performance in delivering very low doses (<10 μg) on a single breath analogous to a metered dose inhaler [ 30 , 31 ].…”
Section: Formulationmentioning
confidence: 99%
“…Scintigraphic studies have shown that when compared to a CFC-based pMDI, lung deposition with a soft mist inhaler is up to 50% higher, and oropharyngeal deposition is lower. 27,28 However, a recent meta-analysis has reported that device use errors similar to those with pMDIs occurred in approximately 60% of patients who used soft mist inhalers. The most common errors were breathing errors, hand-breath coordination, and difficulties with priming the inhalation device.…”
Section: Current Inhalation Delivery Systemsmentioning
confidence: 99%